2013
DOI: 10.1155/2013/218670
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for Large Colorectal Tumor in a Japanese General Hospital

Abstract: Background and Aims. Endoscopic submucosal dissection (ESD) is not widely used in large colorectal lesions because of technical difficulty and possible complications. We aimed to examine the efficacy and safety of ESD for large colorectal neoplasms. Patients and Methods. During the past 5 years, 608 cases of colorectal neoplasm (≧20 mm) were treated by ESD. They were divided into Group A (20–49 mm, 511 cases) and Group B (≧50 mm, 97 cases). Results. The average age, lesion size, and procedure time were 67.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Data on complications after EMR/ESD show similar bleeding rates (EMR 0-11.1%; ESD 0.5-9.5%), but the perforation rate is higher for ESD (1.3-20%) than for EMR (0-5.8%). However, the vast majority of perforations occurring during ESD are small and easily treated during the procedure, and thus the actual need for emergency surgery does not differ for EMR versus ESD [14,18,49,[66][67][68]. ESD is technically demanding and does require long procedure times.…”
Section: Clinical Studies On Colorectal Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on complications after EMR/ESD show similar bleeding rates (EMR 0-11.1%; ESD 0.5-9.5%), but the perforation rate is higher for ESD (1.3-20%) than for EMR (0-5.8%). However, the vast majority of perforations occurring during ESD are small and easily treated during the procedure, and thus the actual need for emergency surgery does not differ for EMR versus ESD [14,18,49,[66][67][68]. ESD is technically demanding and does require long procedure times.…”
Section: Clinical Studies On Colorectal Esdmentioning
confidence: 99%
“…Thus, a recent study comparing 1,029 cases of conventional EMR with 816 ESD procedures showed a significantly higher procedure time for ESD (96 min) than for EMR (18 min). Procedure times increased with the size of the lesion, although for very large lesions a comparison to laparoscopic surgery would be more appropriate [66,67]. Comparative data are available for ESD versus surgery, but again without a formal head-to-head study.…”
Section: Clinical Studies On Colorectal Esdmentioning
confidence: 99%
“…Data on complications after EMR/ESD show similar bleeding rates (EMR 0-11.1%; ESD 0.5-9.5%), but the perforation rate is higher for ESD (1.3-20%) than for EMR (0-5.8%). However, the vast majority of perforations occurring during ESD are small and easily treated during the procedure, and thus the actual need for emergency surgery does not differ for EMR versus ESD [ 31 , 47 , 48 , 49 , 50 , 51 ]. ESD is technically demanding and does require long procedure times.…”
Section: Clinical Studies On Colorectal Esdmentioning
confidence: 99%
“…Thus, a recent study comparing 1,029 cases of conventional EMR with 816 ESD procedures showed a significantly higher procedure time for ESD (96 min) than for EMR (18 min). Procedure times increased with the size of the lesion, although for very large lesions a comparison to laparoscopic surgery would be more appropriate [ 48 , 49 ]. Comparative data are available for ESD versus surgery, but again without a formal head-to-head study.…”
Section: Clinical Studies On Colorectal Esdmentioning
confidence: 99%
“…However, in addition to the stomach, ESD is now applied in the esophagus, large intestine, and duodenum, and as the number of applications in difficult-to-treat cases has grown, so has the number of reports of serious procedural complications. Therefore, the reduction of these complications has become a major issue 2 3 4 5 .…”
Section: Introductionmentioning
confidence: 99%